A carbohydrate-binding protein, B-GRANULE CONTENT 1, influences starch granule size distribution in a dose-dependent manner in polyploid wheat. (21st October 2019) - Chia, Tansy; Chirico, Marcella; King, Rob; Ramirez-Gonzalez, Ricardo; Saccomanno, Benedetta; Seung, David; Simmonds, James; Trick, Martin; Uauy, Cristobal; Verhoeven, Tamara; Trafford, Kay
Abstract: In Triticeae endosperm (e.g. wheat and barley), starch granules have a bimodal size distribution (with A- and B-type granules) whereas in other grasses the endosperm contains starch granules with a unimodal size distribution. Here, we identify the gene, BGC1 ( B-GRANULE CONTENT 1 ), responsible for B-type starch granule content in Aegilops and wheat. Orthologues of this gene are known to influence starch synthesis in diploids such as rice, Arabidopsis, and barley. However, using polyploid Triticeae species, we uncovered a more complex biological role for BGC1 in starch granule initiation: BGC1 represses the initiation of A-granules in early grain development but promotes the initiation of B-granules in mid grain development. We provide evidence that the influence of BGC1 on starch synthesis is dose dependent and show that three very different starch phenotypes are conditioned by the gene dose of BGC1 in polyploid wheat: normal bimodal starch granule morphology; A-granules with few or no B-granules; or polymorphous starch with few normal A- or B-granules. We conclude from this work that BGC1 participates in controlling B-type starch granule initiation in Triticeae endosperm and that its precise effect on granule size and number varies with gene dose and stage of development. Abstract : Reduction in the gene dose of functional BGC1 alleles in Aegilops and wheat results in loss of B-type starch granules but has no deleterious impact on the synthesis of A-granules.